Weavers of tradition and beauty : basketmakers of the Great Basin - Fulkerson, Mary Lee, 1936- (University of Nevada Press, 1995)
Weavers of Tradition and Beauty presents new information on contemporary Native American basketry of the Great Basin, largely from the viewpoint of the weavers themselves. Baskets - and the people who weave them - have always been revered and honored by Native Americans. Fulkerson and Curtis depict, in vivid text and both full color and black-and-white photographs, how their art prevails - even over adverse environmental, social, and economic conditions.